Indicadores de estresse oxidativo e consumo de vitaminas antioxidantes associados à infecção pelo HPV e citologia cervical de um grupo de mulheres - Lazarotto, Angela Khetly (2020)
Most infections triggered by Human Papillomavirus (HPV) are spontaneously eliminated by the immune system. However, part of them have a high viral load and the persistence of the virus oncogenic subtypes are decisive factors for the progression of precancerous lesions. Among the factors that contribute to this condition is the viral ability to intervene in processes that uplift the production of reactive oxygen species (ROS). In the organism, the production of ROS is balanced through the systems of antioxidant enzymes and other antioxidant molecules that assist in this balance. The current study investigated the association between the lipoperoxide plasma levels and the total antioxidant capacity with consumption of vitamins A, C, and E in women from a specialized oncology center. Altogether 113 women with positive and negative outcomes of HPV infection and Pap smear answered questionnaires with socioeconomic data, sexual behavior, food consumption and lifestyle habits. They also underwent the collection for the Pap smear, detection of HPV, and blood tests to determine the lipoperoxidation and the total antioxidant capacity. The XLSTAT-R® and R software were used for statistical analysis. In addition to the mean, median, and standard deviation frequency, according to the type of variable, the Mann-Whitney or Chi-square test were used with subsequent logistic regression. In addition, correlations among lipoperoxidation, total plasma antioxidant capacity and outcomes of Pap smear, HPV and vitamin consumption were determined, leading to the Permutational Analysis of Variance to investigate interactions among them. The prevalence of HPV was 8% and cervical changes were 5.3%. The results point to an increased chance of infection for ex-smokers (OR: 5.07; 95% CI: 0.9388 - 27.3559; p = 0.0592) and for those who use contraceptives (OR = 6.6923; CI95 %: 0.7643 - 58.5999; p = 0.0860). Plasma levels of lipoperoxidation were higher in women without cervical changes (Md: 462400; IIQ: 394642 - 535365; p = 0.015) and in those with HPV (Md: 876855; IIQ: 589295 - 1031243; p = 0.077). The total antioxidant capacity exposed a correlation with the consumption of mate (R2S = 0.196; p = 0.038) and with the levels of lipoperoxides (R2Pearson = -0.262; p = 0.005). However, no interaction was observed between oxidative stress (OS) indicatives and vitamins A, C and E for sexually transmitted infection (STI) and Pap smear outcomes. Lastly, the search for information on the relationship between oxidative stress, antioxidant potential and the consumption of vitamins in individuals who are HPV seropositive or with cervical disorders is scarce, therefore, it is suggested that further studies develop to clarify the relationship or interaction between them.